Pain Medication in Chronic Low Back Pain - Ali Jerjir; Frederik Nietvelt; Iris Smet; Nina D’hondt; Jean-Pierre Van Buyten (Life)
Chronic low back pain (CLBP) significantly impacts individuals’ quality of life and functional abilities. In non-oncological settings, CLBP is often treated for long periods using pharmacotherapy. This paper provides a comprehensive overview of pharmacological treatments for CLBP, detailing their mechanisms of action, adverse effects, and evidence supporting their use. We discuss various medication classes, including NSAIDs, acetaminophen, antidepressants, gabapentinoids, tramadol, major opioids, corticosteroids, antispasticity drugs, benzodiazepines, and antibiotics. Special emphasis is given to the opioid crisis, examining its history, the pathophysiology of opioid tolerance and dependence, the need for cautious opioid use, the key challenges in treatment and emerging medications for CLBP. We also share insights from our experiences with polypharmacy, commonly seen in CLBP patients, at a specialized pain centre in Belgium.